Nickel-based superalloy powder and single crystal additive manufacturing thereof
Through the optimization of the powder components of nickel-based high-temperature alloys and the application of beam shaping technology, combined with the regulation of process parameters, the crack suppression and single crystal preparation problems of nickel-based high-temperature alloy components in additive manufacturing are solved, and a dense and crack-free single crystal structure preparation is achieved.
Patent Information
- Application Number
- CN202411826695.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-12
AI Technical Summary
When manufacturing nickel-based high-temperature alloy components with additive manufacturing, there are problems such as crack suppression, high-temperature gradients in the melt pool that lead to difficulty in preparing single crystals, and difficult to achieve dynamic adjustment of beam shaping technology.
Through component optimization, beam shaping and process parameter regulation, the laser beam is shaped by diffraction optical elements to realize the preparation of single crystal structure of nickel-based high-temperature alloys. Specific measures include adjusting powder composition, using laser beams with flat top spot morphology and optimizing process parameters.
成功实现了致密、无裂纹的镍基高温合金单晶组织的制备,降低了开裂敏感性,改善了熔池形态控制,满足了单晶制备的需求。
Smart Images

Figure CN119614949A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of additive manufacturing, and more particularly to additive manufacturing of nickel-based high-temperature alloy powders. Background Art
[0002] Powder bed-based additive manufacturing (AM) technologies, such as laser powder bed fusion (PBF-LB), use lasers to melt and solidify metal powder layer by layer to achieve high-precision and complex geometry component manufacturing. This technology has many advantages in the production of metal components, including reducing material waste, shortening production cycles, and supporting lightweight design. Therefore, it is widely used in the manufacture of high-performance parts in aerospace, energy, and medical fields.
[0003] High-performance nickel-based high-temperature alloys (γ'-Ni3 (Al, Ti) precipitation-strengthened types, such as classic grades Alloy713 (K418), Alloy738, etc.) are widely used in the aerospace field due to their excellent high-temperature strength, corrosion resistance and creep resistance, especially in extreme working environments such as aircraft engines and gas turbines. The demand for the preparation of such nickel-based high-temperature alloy single crystal components is becoming more urgent. At present, single crystal components are mainly manufactured by directional solidification technology, but this method has problems such as low yield, severe solidification segregation, long processing cycle and low material utilization, and it is difficult to manufacture complex components, which limits its development. In contrast, PBF-LB technology can achieve near-net forming of complex components, which has significant advantages, but it still faces some challenges:
[0004] 1. The high crack sensitivity (difficulty in welding) of γ'-Ni3 (Al, Ti) precipitation-strengthened nickel-based superalloys combined with the inherent high residual stress characteristics of the additive manufacturing process have led to a major technical challenge in the crack suppression of such superalloy components during additive manufacturing. Therefore, how to optimize its composition to reduce crack sensitivity and achieve effective crack suppression under PBF-LB technology still requires in-depth research.
[0005] 2. The existing PBF-LB technology generally uses a Gaussian laser beam with high energy distribution in the center and low energy distribution at the edge in the manufacture of nickel-based high-temperature alloys, which easily causes a high-temperature gradient in the molten pool, resulting in melting characteristics such as deep melting and strong convection, which is not conducive to the preparation of single crystals. Diffractive optical elements (DOEs), as high-diffraction-efficiency optical elements based on diffraction optical theory, have been widely used in beam shaping technology by compensating the phase of the input beam to change the transmission characteristics and intensity of the beam. However, it is still impossible to prepare single crystals of nickel-based high-temperature alloys only by beam shaping without optimizing process parameters (such as spot size and laser energy distribution).
[0006] 3. Existing beam shaping technology is difficult to achieve dynamic adjustment and lacks the ability to switch freely between different spot shapes, especially the lack of technical means to switch DOE without disassembling other original optical paths to reduce repeated installation errors. This deficiency limits the realization of high-degree-of-freedom control of the melting heat flux vector and is difficult to meet the needs of single crystal preparation. Summary of the invention
[0007] The present invention discloses a nickel-based high-temperature alloy powder and an additive manufacturing method and device thereof, which successfully realizes the preparation of a dense, crack-free nickel-based high-temperature alloy single crystal structure through composition optimization, beam shaping and control of process parameters.
[0008] In a first aspect, the present disclosure provides an additively manufactured nickel-based high-temperature alloy component having the following grain boundary structure characteristics: within the grain boundary angle range of 15° to 30°, the grain boundary length density does not exceed 35.2 (1 / mm); within the grain boundary angle range of more than 30°, the grain boundary length density does not exceed 2.6 / (1 / mm).
[0009] In a second aspect, the present disclosure provides a powder for additive manufacturing of the nickel-based high-temperature alloy component described in the first aspect, wherein the composition of the powder comprises the following elements by weight percentage: chromium (Cr): 12wt% to 14wt%, molybdenum (Mo): 4.5wt% to 5.7wt%, niobium (Nb): 1.5wt% to 2.3wt%, aluminum (Al): 5.5wt% to 6.5wt%, titanium (Ti): 0.5wt% to 1wt%, carbon (C): 0.1wt% to 0.28wt%, zirconium (Zr): 0.02wt% to 0.1wt%, boron (B): ≤0.01wt%, silicon (Si): ≤0.5wt%, manganese (Mn): ≤0.25wt%, iron (Fe): ≤2.5wt%, copper (Cu): ≤0.5wt%, nickel (Ni): balance.
[0010] According to a preferred embodiment of the second aspect, the constituent elements of the powder include one or more of the following: C is selected as 0.1wt% to 0.19wt%, Mo is selected as 4.5wt% to 5.1wt%, B is selected as 0.001wt% to 0.01wt%, Zr is selected as 0.05wt% to 0.1wt%, and Nb is selected as 1.8wt% to 2.3wt%.
[0011] In a third aspect, the present disclosure provides a powder for additive manufacturing of the nickel-based high-temperature alloy component of the first aspect, wherein the composition of the powder comprises the following elements by weight percentage: chromium (Cr): 15.7wt% to 16.3wt%, aluminum (Al): 3.2wt% to 3.7wt%, titanium (Ti): 3.2wt% to 3.7wt%, molybdenum (Mo): 1.5wt% to 2.5wt%, niobium (Nb): 0.6wt% to 1.4wt%, zirconium (Zr): 0.02wt% to 0. 1wt%, boron (B): 0.003wt% ~ 0.015wt%, carbon (C): 0.05wt% ~ 0.13wt%, tantalum (Ta): 1.5wt% ~ 2.3wt%, tungsten (W): 2.4wt% ~ 3.0wt%, cobalt (Co): 2.0wt% ~ 8.0wt%, iron (Fe): ≤0.05wt%, manganese (Mn): ≤0.02wt%, silicon (Si): ≤0.3wt%, sulfur (S): ≤0.015wt%, nickel (Ni): balance.
[0012] According to a preferred embodiment of the third aspect, the constituent elements of the powder include one or more of the following: molybdenum (Mo) is selected as 1.6wt% to 2.1wt%, niobium (Nb) is selected as 0.7wt% to 1.2wt%, carbon (C) is selected as 0.08wt% to 0.12wt%, tantalum (Ta) is selected as 1.6wt% to 2.1wt%, tungsten (W) is selected as 2.5wt% to 2.9wt%, zirconium (Zr) is selected as 0.02wt% to 0.07wt%, boron (B) is selected as 0.003wt% to 0.011wt%, and cobalt (Co) is selected as 2.0wt% to 6.0wt%.
[0013] According to a preferred implementation of the third aspect, aluminum + titanium (Al + Ti) is selected to be 6.5wt% to 7.4wt%.
[0014] In a fourth aspect, the present disclosure provides a method for additive manufacturing of a nickel-based high-temperature alloy single crystal component formed by powder according to any one of the second aspect or the third aspect, the method comprising: according to a preset scanning path and process parameters, controlling a laser beam that is shaped by a diffractive optical element in the form of a flat-top spot at least during the additive manufacturing process, and selectively melting the powder layer by layer on a substrate to form stacked and consolidated layers until the manufacture of the single crystal component is completed.
[0015] According to a preferred embodiment of the fourth aspect, the process parameters include one or more of laser power 50-500W, laser scanning speed 50-1500mm / s, scanning line spacing 0.02-0.18mm, layer thickness 40-60μm, spot diameter 50-1000μm, ratio of molten pool width to molten pool depth 2-5, ratio of molten pool width to scanning line spacing 2-5 and ratio of molten pool depth to layer thickness 1.1-3.
[0016] In a fifth aspect, the present disclosure provides a device for realizing the switching of the diffractive optical element in the method described in any one of the fourth aspects, wherein the device is constructed in the optical path before the laser beam enters the deflection mirror and is configured to include: a supporting portion, which is fixed in the optical path; a separating portion, which is detachably fixed to the supporting portion; and a mounting portion, which is fixed to the separating portion and is used to mount the diffractive optical element; wherein, when switching the diffractive optical element, the diffractive optical element is separated from the optical path by removing the separating portion from the supporting portion.
[0017] According to a preferred implementation of the fifth aspect, the supporting portion is fixed between the beam expander and the deflection mirror in the optical path and is not disassembled when the diffractive optical element is switched.
[0018] According to a preferred implementation of the fifth aspect, the mounting portion includes at least one displacement adjuster for adjusting the displacement of the diffractive optical element in the X-axis and / or Y-axis direction.
[0019] According to a preferred implementation of the fifth aspect, the separation portion is embedded in the support portion so that the diffractive optical element is embedded in at least a portion of the groove of the support portion in an installed state.
[0020] In a sixth aspect, the present disclosure provides an additive manufacturing device comprising the apparatus described in any one of the fifth aspects.
[0021] It is to be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings, which are incorporated herein and form a part of the specification, illustrate one or more embodiments of the present disclosure and, together with the description, serve to explain the principles of the present disclosure and to enable one of ordinary skill in the relevant art to make and use the present disclosure.
[0023] Figure 1 A schematic diagram of an additive manufacturing device according to an embodiment of the present disclosure is shown;
[0024] Figure 2A cross-sectional image of a nickel-based high-temperature alloy component specimen prepared according to Test Example 1 of the present disclosure is shown;
[0025] Figure 3 The crystal orientation characterization result of the SEM-EBSD test on the cross section of the sample prepared according to Test Example 1 of the present disclosure is shown;
[0026] Figure 4 The crystal orientation characterization result of the SEM-EBSD test on the cross section of the sample prepared according to Test Example 2 of the present disclosure is shown;
[0027] Figure 5 A schematic diagram of the exploded structure of the DOE fast switching device in the optical path according to an embodiment of the present disclosure is shown;
[0028] Figure 6 A schematic diagram of the structure of the DOE fast switching device in the optical path in use state according to an embodiment of the present disclosure is shown;
[0029] Figure 7 A schematic diagram of the structure of a local use state of a DOE fast switching device in an optical path according to an embodiment of the present disclosure is shown. DETAILED DESCRIPTION
[0030] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments may be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; rather, the description of these embodiments is intended to make the present disclosure more comprehensive and complete and to fully convey the concepts of the example embodiments to those skilled in the art. The described features, structures, or characteristics may be combined in any suitable manner in one or more embodiments. In the following description, many specific details are provided to provide a deeper understanding of the embodiments of the present disclosure.
[0031] The "additive manufacturing (AM)" described in this disclosure is a 3D printing technology that manufactures components by adding powder materials layer by layer and melting and solidifying the powder materials layer by layer using a laser beam. This technology is based on a digital model generated by computer-aided design (CAD) software, and accurately controls the melting and solidification process of each layer of material, thereby gradually manufacturing a complete component.
[0032] Nickel-based high temperature alloy powder (Alloy713(K418))
[0033] As previously described in the background technology, nickel-based high-temperature alloys, especially γ' precipitation-strengthened high-performance nickel-based high-temperature alloys (such as Alloy713 (K418)), are prone to significant cracking during the PBF-LB process due to the inherent high cracking sensitivity of the material and the inherent high residual stress of the process. Therefore, it is necessary to finely optimize its composition to reduce the cracking sensitivity so as to effectively control and inhibit crack formation in additive manufacturing. Some embodiments of the present disclosure involve optimizing the composition of nickel-based high-temperature alloy powders, and in particular, optimizing the composition of difficult-to-weld nickel-based high-temperature alloys such as the classic grade Alloy713 (K418) to reduce cracking sensitivity, so as to achieve effective cracking inhibition of components under PBF-LB technology. The composition optimization disclosed in the present disclosure mainly involves increasing the content of carbon (C) and molybdenum (Mo) elements and reducing the content of boron (B), zirconium (Zr) and niobium (Nb) elements.
[0034] (Before optimization)
[0035] Generally speaking, the nickel-based high-temperature alloy powder composition before optimization includes, by weight percentage, 12wt% to 14wt% chromium (Cr), 3.8wt% to 5.2wt% molybdenum (Mo), 1.8wt% to 2.8wt% niobium (Nb), 5.5wt% to 6.5wt% aluminum (Al), 0.5wt% to 1wt% titanium (Ti), 0.08wt% to 0.2wt% carbon (C), 0.05wt% to 0.15wt% zirconium (Zr), 0.005wt% to 0.015wt% boron (B), ≤0.5wt% silicon (Si), ≤0.25wt% manganese (Mn), ≤2.5wt% iron (Fe), ≤0.5wt% copper (Cu) and the balance nickel (Ni).
[0036] In one example, the nickel-based high-temperature alloy powder composition before optimization includes, by weight percentage, 13wt% Cr, 4.5wt% Mo, 2.3wt% Nb, 6wt% Al, 0.75wt% Ti, 0.14wt% C, 0.01wt% B, 0.1wt% Zr, 0.25wt% Si, 0.125wt% Mn, 1.25wt% Fe, 0.25wt% Cu, and the balance Ni.
[0037] This composition design is already able to provide good high-temperature strength and corrosion resistance, but its tendency to crack during additive manufacturing, especially laser melting, is still significant.
[0038] (After optimization)
[0039] Generally speaking, the optimized nickel-based high-temperature alloy powder composition includes, by weight percentage, 12wt% to 14wt% Cr, 4.5wt% to 5.7wt% Mo, 1.5wt% to 2.3wt% Nb, 5.5wt% to 6.5wt% Al, 0.5wt% to 1wt% Ti, 0.1wt% to 0.28wt% C, 0.02wt% to 0.1wt% Zr, ≤0.01wt% B, ≤0.5wt% Si, ≤0.25wt% Mn, ≤2.5wt% Fe, ≤0.5wt% Cu and the balance Ni.
[0040] In a preferred embodiment, the C, Mo, B, Zr, Nb or a combination thereof of the optimized nickel-based high-temperature alloy powder is selected to be 0.1wt% to 0.19wt% of C, 4.5wt% to 5.1wt% of Mo, 0.001wt% to 0.01wt% of B, 0.05wt% to 0.1wt% of Zr and 1.8wt% to 2.3wt% of Nb.
[0041] In one example, the optimized nickel-based high-temperature alloy powder composition includes, by weight percentage, 13wt% Cr, 5.1wt% Mo, 1.9wt% Nb, 6wt% Al, 0.75wt% Ti, 0.19wt% C, 0.005wt% B, 0.06wt% Zr, 0.25wt% Si, 0.125wt% Mn, 1.25wt% Fe, 0.25wt% Cu, and the balance Ni.
[0042] In one example, the optimized nickel-based high-temperature alloy powder composition includes, by weight percentage, 13wt% Cr, 4.8wt% Mo, 2.05wt% Nb, 6wt% Al, 0.75wt% Ti, 0.145wt% C, 0.0055wt% B, 0.075wt% Zr, 0.25wt% Si, 0.125wt% Mn, 1.25wt% Fe, 0.25wt% Cu, and the balance Ni.
[0043] In the specific implementation process, the performance of the nickel-based high-temperature alloy powder after composition optimization in PBF-LB is particularly outstanding, especially in reducing the tendency of cracking while ensuring the overall performance of the material. This optimization is not only aimed at adjusting a single element, but also controls the interaction between multiple elements to achieve a comprehensive improvement in performance.
[0044] C is a key element for forming carbides, which can effectively prevent the slip of grain boundaries, thereby improving the high-temperature strength and creep resistance of the material. In the optimized components, the appropriate increase in C content (controlled at 0.1wt% to 0.28wt%, especially controlled at 0.1wt% to 0.19wt%) not only improves the high-temperature mechanical properties of the alloy, but also consumes the solidification segregation elements at the grain boundaries to a certain extent by forming carbides to reduce the cracking sensitivity of the material. Mo, as a strong solid solution strengthening element, can not only improve the creep resistance of the alloy, but also reduce the plastic deformation of the material in the high temperature range; at the same time, Mo is also a carbide-forming element. By appropriately increasing the Mo content (controlled at 4.5wt% to 5.7wt%, especially controlled at 4.5wt% to 5.1wt%), not only the high-temperature mechanical properties of the alloy are improved, but also the amount of carbide formation is optimized to reduce the cracking sensitivity of the material.
[0045] B and Zr are usually used as grain boundary strengthening elements in alloys, which can improve the grain boundary strength and high temperature performance of the material. However, excessive B and Zr will increase the cracking sensitivity of the alloy, especially in additive manufacturing, where higher B and Zr contents will induce liquefaction cracking effects. During the optimization process, the cracking sensitivity of the alloy was significantly reduced by reducing the B content to ≤0.01wt% (especially controlled at 0.001wt% to 0.01wt%) and controlling the Zr content to 0.02wt%-0.1wt% (especially controlled at 0.05wt% to 0.1wt%). This reduction not only did not significantly affect the high temperature properties of the alloy, but also enabled it to achieve crack suppression during the PBF-LB process. As an important γ' strengthening phase stabilizing element, Nb was also moderately reduced during the optimization process. Before optimization, the Nb content was between 1.8wt% and 2.8wt%, while after optimization, the Nb content was reduced to 1.5wt% to 2.3wt%, especially to 1.8wt% to 2.3wt%, which can reduce the solidification segregation of Nb and thus reduce the cracking sensitivity of the alloy.
[0046] By adjusting the above elements, the cracking sensitivity of nickel-based high-temperature alloys during the PBF-LB process is significantly reduced, which is crucial for cracking suppression.
[0047] In addition, the nickel-based high-temperature alloy powder with optimized composition also meets the requirements for single crystal preparation. The optimized powder, combined with the PBF-LB process including DOE beam shaping technology, can achieve precise shaping and control of the molten pool, and then achieve dynamic single crystal selection, to obtain a single crystal structure with strong texture and no large-angle grain boundaries, or a near-single crystal structure with strong texture but a small amount of large-angle grain boundaries. Such a single crystal / near-single crystal structure can maintain excellent mechanical properties (high strength and creep resistance) in a high-temperature environment, and its single crystal / near-single crystal components are crucial in the hot end of aircraft engines and gas turbines.
[0048] Nickel-based high temperature alloy powder (Alloy738)
[0049] Some embodiments of the present disclosure are directed to optimizing the composition of nickel-based high-temperature alloy powders, and in particular, to optimizing the composition of difficult-to-weld nickel-based high-temperature alloys such as the classic Alloy 738 to reduce crack sensitivity, so as to achieve effective crack suppression of components under PBF-LB technology. The composition optimization of the present disclosure mainly involves increasing the content of Mo, Nb, C, Ta and W elements and reducing the content of boron Zr, B and Co elements.
[0050] (Before optimization)
[0051] Generally speaking, the composition of the nickel-based high-temperature alloy powder before optimization includes, by weight percentage, 15.7wt% to 16.3wt% Cr, 3.2wt% to 3.7wt% Al, 3.2wt% to 3.7wt% Ti, 1.5wt% to 2.0wt% Mo, 0.6wt% to 1.1wt% Nb, 0.05wt% to 0.15wt% Zr, 0.005wt% to 0.015wt% B, 0.15wt% to 0.2wt% C, 1.5wt% to 2.0wt% Ta, 2.4wt% to 2.8wt% W, 8.0wt% to 9.0wt% Co, ≤0.05wt% Fe, ≤0.02wt% Mn, ≤0.3wt% Si, ≤0.015wt% S and the balance Ni.
[0052] In one example, the nickel-based high-temperature alloy powder composition before optimization includes, by weight percentage, 16wt% Cr, 3.45wt% Al, 3.45wt% Ti, 1.75wt% Mo, 0.85wt% Nb, 0.1wt% Zr, 0.01wt% B, 0.175wt% C, 1.75wt% Ta, 2.6wt% W, 8.5wt% Co, 0.025wt% Fe, 0.01wt% Mn, 0.15wt% Si, 0.0075wt% S and the balance Ni.
[0053] (After optimization)
[0054] Generally speaking, the optimized nickel-based high-temperature alloy powder composition includes, by weight percentage, 15.7wt% to 16.3wt% Cr, 3.2wt% to 3.7wt% Al, 3.2wt% to 3.7wt% Ti, 1.5wt% to 2.5wt% Mo, 0.6wt% to 1.4wt% Nb, 0.02wt% to 0.1wt% Zr, 0.003wt% to 0.015wt% B, 0.05wt% to 0.13wt% C, 1.5wt% to 2.3wt% Ta, 2.4wt% to 3.0wt% W, 2.0wt% to 8.0wt% Co, ≤0.05wt% Fe, ≤0.02wt% Mn, ≤0.3wt% Si, ≤0.015wt% S and the balance Ni.
[0055] In a preferred embodiment, the Mo, Nb, B, Zr, Nb or a combination thereof of the optimized nickel-based high-temperature alloy powder is selected to be 1.6wt% to 2.1wt% Mo, 0.7wt% to 1.2wt% Nb, 0.08wt% to 0.12wt% C, 1.6wt% to 2.1wt% Ta, 2.5wt% to 2.9wt% W, 0.02wt% to 0.07wt% Zr, 0.003wt% to 0.011wt% B and 2.0wt% to 6.0wt% Co.
[0056] In a preferred embodiment, the combination of aluminum and titanium (Al+Ti) is selected to be 6.5 wt% to 7.4 wt%.
[0057] In one example, the optimized nickel-based high-temperature alloy powder composition includes, by weight percentage, 16wt% Cr, 3.45wt% Al, 3.45wt% Ti, 2wt% Mo, 1wt% Nb, 0.06wt% Zr, 0.009wt% B, 0.09wt% C, 1.9wt% Ta, 2.7wt% W, 5wt% Co, 0.025wt% Fe, 0.01wt% Mn, 0.15wt% Si, 0.0075wt% S and the balance Ni.
[0058] In the optimized components, by controlling the C content at 0.05wt% to 0.13wt%, especially at 0.08wt% to 0.12wt%, not only the high temperature mechanical properties of the alloy are improved, but also the solidification segregation elements at the grain boundaries are consumed to a certain extent by forming carbides to reduce the cracking sensitivity of the material. As a strong solid solution strengthening element, Mo can not only improve the creep resistance of the alloy, but also reduce the plastic deformation of the material in the high temperature range; at the same time, Mo is also a carbide forming element. By controlling the Mo content at 1.5wt% to 2.5wt%, especially at 1.6wt% to 2.1wt%, the high temperature strength of the material can be effectively improved while reducing the cracking sensitivity. Nb is an important element for forming the γ' strengthening phase, which can promote the formation and stability of the strengthening phase in the alloy, thereby improving the strength and hardness under high temperature conditions. However, too high a Nb content will lead to solidification segregation and increase the risk of cracking. Therefore, after optimization, the content of Nb is increased to 0.6wt% to 1.4wt%, preferably 0.7wt% to 1.2wt%, to achieve a balance between strength and toughness, and ensure that Alloy738 has good crack resistance during the PBF-LB process. Ta and W, as effective γ' strengthening phase elements, can further enhance the high temperature strength and hardness of the alloy. Ta is increased to 1.5wt% to 2.3wt%, especially controlled at 1.6wt% to 2.1wt% in the preferred embodiment, while W is increased to 2.4wt% to 3.0wt%, preferably 2.5wt% to 2.9wt%, which can improve the material's resistance to high temperature deformation and reduce the cracking tendency caused by thermal cycling, so as to facilitate the formation of a stable strengthening phase structure during the PBF-LB process and inhibit the generation of cracks.
[0059] Zr and B are grain boundary strengthening elements in nickel-based alloys, which can improve the grain boundary strength and high temperature performance of the material. However, excessive Zr and B content can cause liquefaction cracking during additive manufacturing, especially during rapid heating and cooling. By controlling the Zr content to 0.02wt% to 0.1wt%, particularly preferably 0.02wt% to 0.07wt%, and reducing the B content to 0.003wt% to 0.015wt%, particularly preferably 0.003wt% to 0.011wt%, the cracking sensitivity can be effectively reduced without affecting the high temperature performance of the material. Co can improve the oxidation resistance in nickel-based alloys, but its excessive content will affect the thermal stability of the material and produce higher residual stresses during the PBF-LB process, thereby increasing the risk of cracking. Therefore, by reducing the Co content to 2.0wt% to 8.0wt%, particularly preferably 2.0wt% to 6.0wt%, the influence of residual stress can be significantly reduced, while retaining the necessary oxidation resistance and improving the applicability in PBF-LB.
[0060] Al and Ti are key elements of the γ' strengthening phase and have an important influence on the high temperature strength and organizational stability of the alloy. By optimizing the combined content of Al and Ti to 6.5wt% to 7.4wt%, a stable γ' phase distribution can be obtained during the PBF-LB process, further improving the high temperature strength and creep resistance of the material while effectively reducing the crack tendency.
[0061] Through the above-mentioned composition optimization, the cracking sensitivity of Alloy738 powder in the PBF-LB process has been significantly reduced. The optimized alloy can maintain high temperature strength and creep resistance while reducing cracking, so it is suitable for the preparation of single crystal or near-single crystal structures in additive manufacturing.
[0062] PBF-LB process
[0063] According to an embodiment of the present disclosure, the PBF-LB process described is a method for performing PBF-LB additive manufacturing on any of the optimized nickel-based high-temperature alloy powders provided above to form a nickel-based high-temperature alloy single crystal component, that is, a 3D printing method for a nickel-based high-temperature alloy single crystal component. The method generally involves controlling a laser beam in the form of a flat-top spot that is shaped by a diffractive optical element (DOE) at least during the additive manufacturing process according to a preset scanning path and process parameters, and selectively melting the nickel-based high-temperature alloy powders layered on a substrate to form stacked and consolidated layers until the manufacturing of the single crystal component is completed.
[0064] Figure 1 Schematic diagram of additive manufacturing equipment according to an embodiment of the present disclosure is shown. It should be understood that the above-mentioned 3D printing method involved in the present disclosure is to use Figure 1 The conventional 3D printing method mainly involves driving the following operations using a control system 18: driving the powder in the powder storage 12 to be supplied to the working plane 19 of the printing chamber 11 or, in other embodiments, using a powder drop container arranged in the printing chamber 11 to release the powder on the substrate 14, and then driving the powder spreading device 16 (blade / roller) to move along the working plane to evenly cover the powder on the substrate 14 with a powder layer having a specific layer thickness, and then driving the laser beam to selectively melt the powder layer spread on the substrate 14 according to the preset scanning path and process parameters (configured in the 3D model) to form a solidified layer, and then driving the forming cylinder 13 to descend a layer thickness and continue to supply powder, spread powder and melt the powder layer, accumulating layer by layer until the forming preparation of the component 17 matching the designed 3D model structure is completed on the substrate 14 (i.e., in the powder bed 15). In addition, some other operations are also involved, such as the supply and control of protective gas and wind field, monitoring of the printing process, etc., which will not be expanded one by one here.
[0065] It should be understood that the laser beam can only achieve precise melting scanning on the powder layer after being processed by various optical elements configured in the optical path. The optical elements configured in the optical path include, for example, a laser 21, a collimator 22, a beam expander 23 (which may also be eliminated in other embodiments), a deflection mirror 25 (galvanometer) and a focusing mirror 26 (F-Theta lens) in sequence along the propagation path of the laser beam. After the laser beam is emitted from the laser 21, it is collimated by the collimator 22, expanded in diameter by the beam expander 23, deflected by the deflection mirror 25 and focused by the focusing mirror 26 to irradiate the powder layer.
[0066] According to the embodiment of the PBF-LB process disclosed in the present invention, a diffractive optical element 24 (DOE) is configured in the optical path. The diffractive optical element 24 can be configured in the optical path between the beam expander 23 and the deflection mirror 25, for example, to shape the laser beam emitted from the beam expander 23 from a Gaussian laser beam with a Gaussian distribution of the spot to a flat-top laser beam with a flat-top distribution of the spot (for example, a circular flat-top laser beam), and the shaped laser beam then passes through the deflection mirror 25 and the focusing mirror 26 in sequence to irradiate the powder layer.
[0067] The present disclosure introduces beam shaping technology into the PBF-LB process to manufacture nickel-based high-temperature alloy single crystal components, which can significantly improve the control ability of the molten pool morphology and the flexibility of adjusting the heat flux vector at the solidification front. It should be understood that the traditional Gaussian laser beam will produce a high temperature gradient during the melting process, which is easy to cause deep melting and strong convection, which is very unfavorable for the growth of single crystals. By using the diffractive optical element 24 to shape the laser beam into a flat-top distribution, the laser energy can be more evenly distributed in the molten pool, the temperature gradient of the molten pool is reduced, and the Marangoni convection is reduced. In addition, the flat-top laser beam not only improves the dynamic behavior of the molten pool, but also the resulting heat conduction molten pool promotes a stable and controllable melting and solidification process. Because the molten pool contour and solidification direction are more stable, and the molten pool width-to-depth ratio is larger, the material can grow better along the construction direction during solidification, which is crucial for the formation of strong textures along the construction direction. At the same time, the optimized flat-top spot size and the precise matching of other PBF-LB process parameters cause the solidification heat flux vector to periodically deflect to at least two of the target single crystal orientation configurations. <100> crystal orientation, thereby inducing the single crystal dynamic crystal selection effect, which is crucial for the formation of single crystal / near single crystal structure.
[0068] The present invention discloses a systematic process optimization for difficult-to-weld nickel-based high-temperature alloys represented by Alloy713 (K418) and Alloy738, aiming to effectively control the melting heat flux vector to achieve dense, crack-free single crystal / near single crystal PBF-LB additive manufacturing.
[0069] According to the implementation of the PBF-LB process disclosed in the present invention, the process optimization design scheme not only introduces DOE to shape the spot shape of the laser beam into a flat-top spot, but also involves the optimization of process parameters. The optimized process parameters include 50-500W laser power, 50-1500mm / s laser scanning speed, 0.02-0.18mm scanning line spacing, 40-60μm layer thickness and 50-1000μm spot diameter, etc. The precise control of these parameters not only affects the efficiency of the melting process, but is also directly related to the microstructure and performance of the final component.
[0070] For example, in a specific example, the optimized process parameters are set to 380W laser power, 500mm / s laser scanning speed, 0.055mm scanning line spacing, 60μm layer thickness, and 200μm spot diameter. This combination not only achieves a good balance between energy input and material melting, but also ensures full bonding between the layers, which is beneficial to the density and uniformity of the final component. Through this process optimization, the preparation of single crystal components can be carried out with higher precision and lower defect rate.
[0071] According to the implementation of the PBF-LB process disclosed herein, the optimized process parameters also include: a ratio of molten pool width to molten pool depth of 2 to 5, a ratio of molten pool width to scan line spacing of 2 to 5, and a ratio of molten pool depth to layer thickness of 1.1 to 3.
[0072] It should be understood that controlling the ratio of the molten pool width to the depth between 2 and 5 can maintain the balanced shape of the molten pool, avoid the molten pool being too deep or too shallow, and facilitate the control of the heat flux vector during melting to reduce crack sensitivity. Controlling the ratio of the molten pool width to the scanning line spacing between 2 and 5 can make the overlap of the molten pool sufficient and not excessive, thereby improving the interlayer bonding effect and the density of the component. Controlling the ratio of the molten pool depth to the layer thickness between 1.1 and 3 can enable the molten pool to achieve full melting and good metallurgical bonding during the deposition of each layer to obtain a dense and uniform component structure. By reasonably controlling these three geometric ratios, the optimized PBF-LB process can achieve morphological stability and uniformity of energy input in the molten pool, making the melting process more controlled, and providing process support for the realization of single crystal or near-single crystal components.
[0073] Test Example 1
[0074] According to a specific test example of the present disclosure, the nickel-based high-temperature alloy powder described above (optimized Alloy713 (K418)) was used, and the composition was selected as 13wt% Cr, 4.8wt% Mo, 2.05wt% Nb, 6wt% Al, 0.75wt% Ti, 0.145wt% C, 0.0055wt% B, 0.075wt% Zr, 0.25wt% Si, 0.125wt% Mn, 1.25wt% Fe, 0.25wt% Cu and the balance Ni as the powder raw material of the PBF-LB process. The material was prepared and the DOE shaping scheme described above was introduced in the PBF-LB process to shape the Gaussian laser beam into a circular flat-top laser beam. At the same time, the optimized process parameters were adopted, and the laser power of 380 W, the laser scanning speed of 500 mm / s, the scanning line spacing of 0.055 mm, the layer thickness of 60 μm and the spot diameter of 200 μm were selected for specific melting scanning control. During the scanning process, the ratio of the molten pool width to the molten pool depth was controlled to be 3.4, the ratio of the molten pool width to the scanning line spacing was 4.6, and the ratio of the molten pool depth to the layer thickness was 1.3. Finally, the nickel-based high-temperature alloy component specimens were prepared.
[0075] Tissue Characterization of Test Case 1
[0076] The prepared nickel-based high-temperature alloy component samples were sampled by electric spark wire cutting, and the samples were ground and polished according to the standard metallographic sample preparation method. Observation was performed using an optical microscope, such as Figure 2 As shown in the figure, there are no cracks on the surface of the sample, only a small amount of pores caused by insufficient fusion, and the density can reach more than 98%. Figure 3 As shown in the figure, SEM-EBSD test was performed on the range of 600μm×1200μm inside the sample, and the results showed that the sample showed a near-single crystal structure. The grain boundary angle is a key parameter for describing single crystal / near-single crystal / polycrystalline materials. It refers to the difference in crystal orientation between two adjacent grains, expressed as an angle. When the maximum grain boundary angle is less than 15°, the material is defined as a single crystal; when the maximum grain boundary angle is less than 30°, the material is defined as a near-single crystal. The nickel-based high-temperature alloy described above was manufactured using conventional processes. The unit area grain boundary length density of the sample in the range of 15° to 30° was 14.8 (1 / mm), and the unit area grain boundary length density above 30° was 16.7 (1 / mm). The nickel-based high-temperature alloy described above was manufactured using the process provided in Test Example 1 of the present disclosure. The grain boundary length density per unit area of the sample in the range of 15° to 30° was 26.39 (1 / mm), and the grain boundary length density per unit area above 30° was 1.81 (1 / mm). The grain boundaries above 30° were basically eliminated, indicating that the sample had a near-single crystal structure.
[0077] It should be understood that grain boundary length density refers to the total length of grain boundaries per unit area, and is usually used to express the number or length density of grain boundaries. The unit "1 / mm" represents the concept of grain boundary length density - that is, per unit area (mm 2 ) is the total length of the grain boundary in the sample (mm). This unit expression is derived from the ratio of length to area in the calculation (mm / mm 2 ), thus simplifying to 1 / mm.
[0078] In microstructural characterization, MUD (Maximum Uniform Density) usually reflects texture strength. Specifically, MUD is used to quantify the preference of grains for a specific orientation. The higher the MUD value, the more concentrated the grains are oriented in a specific direction, and the greater the texture strength; the lower the MUD value, the more uniform and random the grain orientation distribution is, and the weaker the texture strength is. The nickel-based high-temperature alloy described above was manufactured using conventional processes, and the MUD value of the sample was 10; while the nickel-based high-temperature alloy described above was manufactured using the process provided in Test Example 1 of the present disclosure, the MUD value of the sample was 16. This shows that the sample prepared using the technology disclosed in the present disclosure has a strong texture.
[0079] Test Example 2
[0080] According to a specific test example of the present disclosure, the nickel-based high-temperature alloy powder described above (optimized Alloy738) was used, and the composition was selected as 16wt% Cr, 3.45wt% Al, 3.45wt% Ti, 2wt% Mo, 1wt% Nb, 0.06wt% Zr, 0.009wt% B, 0.09wt% C, 1.9wt% Ta, 2.7wt% W, 5wt% Co, 0.025wt% Fe, 0.01wt% Mn, 0.15wt% Si, 0.0075wt% S and the balance Ni as PBF-L The powder raw material of process B was used, and the DOE shaping scheme described above was introduced in the PBF-LB process to shape the Gaussian laser beam into a circular flat-top laser beam. At the same time, the optimized process parameters were adopted, and the laser power of 390 W, the laser scanning speed of 1050 mm / s, the scanning line spacing of 0.177 mm, the layer thickness of 40 μm and the spot diameter of 200 μm were selected for specific melting scanning control. During the scanning process, the ratio of the molten pool width to the molten pool depth was controlled to be 3.6, the ratio of the molten pool width to the scanning line spacing was 2.7, and the ratio of the molten pool depth to the layer thickness was 2.3. Finally, the nickel-based high-temperature alloy component specimens were prepared.
[0081] Tissue Characterization of Test Case 2
[0082] like Figure 4As shown, SEM-EBSD test was performed on the range of 513μm×1138μm inside the sample, and the results showed that the interior of the sample showed a near-single crystal structure. The nickel-based high-temperature alloy described above was manufactured using the process provided in Test Example 2 of the present disclosure. The grain boundary length density per unit area of the sample in the range of 15° to 30° was 35.12 (1 / mm), and the grain boundary length density per unit area above 30° was 2.52 (1 / mm). The grain boundaries above 30° were basically eliminated, indicating that the sample had a near-single crystal structure. The nickel-based high-temperature alloy described above was manufactured using a conventional process, and the MUD value of the sample was 10; while the nickel-based high-temperature alloy described above was manufactured using the process provided in Test Example 2 of the present disclosure, the MUD value of the sample was 17, indicating that the sample prepared using the technology disclosed in the present disclosure has a strong texture.
[0083] It can be seen from Test Example 1 and Test Example 2 that the preparation of single crystal structure was successfully achieved through the aforementioned composition optimization, beam shaping and process parameter regulation. Composition optimization makes the high-temperature phase transformation behavior of the alloy more controllable, reduces the cracking sensitivity of the material, enhances its fluidity, and promotes the uniform bonding between molten layers. Secondly, the flat-top laser beam shaping technology is used to significantly improve the thermal field distribution of the molten pool, reduce the temperature gradient, reduce thermal stress, and thus help to form a uniform solidification structure. This uniformity effectively prevents macroscopic stress concentration caused by local overheating or cooling during the crystallization process. Finally, the optimized process parameters make the melting and solidification processes more coordinated, thereby achieving good fusion and mutual influence between each layer.
[0084] The nickel-based high-temperature alloy single crystal component disclosed in the present invention has achieved specific grain boundary structure characteristics through composition design and optimization of laser powder bed melting (PBF-LB) process parameters, that is, the grain boundary length density is high in the low angle range, and significantly reduced in the high angle range. Specifically, the grain boundary length density of the nickel-based high-temperature alloy single crystal component disclosed in the present invention is effectively controlled to not exceed 35.2 (1 / mm) in the grain boundary angle range of 15° to 30°; and in the grain boundary angle range of more than 30°, the grain boundary length density is further controlled to not exceed 2.6 (1 / mm). It can be seen that the number of grain boundaries with large angle differences is extremely small or even almost disappears. This feature reflects the high consistency of the grain orientation inside the component, that is, the organizational characteristics close to single crystals.
[0085] From the perspective of microstructure, the grain boundary distribution pattern disclosed in the present invention shows that the orientation differences between most grains in the material are small, concentrated in the range of 15° to 30°, while high-angle grain boundaries exceeding 30° are greatly reduced or even eliminated. Such a significantly reduced density of high-angle grain boundaries can reduce stress concentration points inside the material and avoid microscopic failure mechanisms such as grain boundary sliding that lead to cracking under high temperature or mechanical load, thereby improving the material's high-temperature strength, creep resistance, and crack resistance. At the same time, this distribution method further enhances the material's resistance to thermal fatigue, especially in high-temperature fluctuation environments. Overall, the single crystal components prepared by the process disclosed in the present invention have been optimized in performance, achieving excellent thermal stability and high-temperature performance.
[0086] DOE fast switching device
[0087] In order to realize free switching between different spot shapes (circular Gaussian spot / circular / triangular / rectangular flat-top spot) and reduce the repeated installation error when switching DOE, so as to better meet the spot shape required for the preparation of nickel-based high-temperature alloy single crystals, the present disclosure also relates to a device for realizing fast switching of DOE. The device is used as a part of the structure of the additive manufacturing device disclosed in the present disclosure.
[0088] Figure 5 FIG. 1 shows a schematic diagram of the exploded structure of the DOE fast switching device in the optical path according to an embodiment of the present disclosure. Figure 6 The figure shows a schematic diagram of the structure of the DOE fast switching device in the optical path according to the embodiment of the present disclosure. Figure 7 FIG. 1 shows a schematic diagram of a local use state of a DOE fast switching device in an optical path according to an embodiment of the present disclosure. Figure 5-7 The device is arranged in the optical path before the laser beam enters the deflection mirror 25, and more specifically, in the optical path between the beam expander 23 and the deflection mirror 25 (it should be understood that in the optical path where the beam expander 23 is not configured, the device can be arranged in the optical path between the collimator 22 and the deflection mirror 25).
[0089] The device comprises a supporting part 31, a separating part 32 and a mounting part 33. The supporting part 31 is fixed in the optical path, the separating part 32 is detachably fixed on the supporting part 31, and the mounting part 33 is fixed on the separating part 32 and is used to mount the diffractive optical element.
[0090] Specifically, the support portion 31 is fixed to the beam expander 23 and the deflection mirror 25 respectively by two long positioning pins 34a and 34b for positioning and two long screws 35a and 35b for fixing, wherein the beam expander 23 is sleeved in the connecting plate 30, and the long positioning pins 34a and 34b and the long screws 35a and 35b are passed through the connecting plate 30 to fix the support portion 31 and the deflection mirror 25. The separation portion 32 is fixed to the support portion 31 by two short positioning pins 36a and 36b for positioning and two short screws 37a and 37b for fixing.
[0091] When switching DOE, the support part 31 remains fixed between the beam expander 23 and the deflection mirror 25 in the optical path without being disassembled, and the DOE is separated from the optical path by disassembling the separation part 32 from the support part 31. Specifically, when switching DOE, the support part 31 is fixed in the optical path without being disassembled, and the mounting part 33 is fixed on the separation part 32 without being disassembled. By disassembling the short positioning pins 36a, 36b and the short screws 37a, 37b between the support part 31 and the separation part 32, the separation part 32 can be separated from the support part 31, that is, the DOE is separated from the optical path, thereby achieving the switching of DOE without disassembling other original optical path components, and reducing the repeated installation error when switching DOE. This switching mechanism not only improves the convenience of operation, but also provides strong technical support for the efficient manufacturing of high-performance nickel-based high-temperature alloy single crystal parts.
[0092] In some examples, the separation portion 32 is embedded with the support portion 31, so that the DOE is embedded in at least a portion of the groove of the support portion 31 in the installed state, so as to effectively utilize the space and meet the demand for DOE switching in a smaller design space. In the optical path, any slight displacement or deviation may affect the quality and characteristics of the final light beam, and the embedded setting can provide higher mechanical stability in a fixed state, ensuring that during the transmission of the laser beam, the propagation path and quality of the beam will not be affected by external vibration or improper operation.
[0093] In some examples, the mounting portion 33 also includes a displacement regulator 33a and / or a displacement regulator 33b to achieve high-precision fine-tuning of the DOE position in the X-axis and / or Y-axis directions. Among them, the displacement regulator 33a is configured to adjust the displacement of the DOE in the Y-axis direction, and the displacement regulator 33b is configured to adjust the displacement of the DOE in the X-axis direction. This two-way adjustment function enables the propagation path of the laser beam to be accurately controlled after switching the DOE, ensuring the stability of the spot shape and improving the accuracy of the optical system. In addition, the mounting portion 33 also includes a built-in threaded retaining ring 33c for fixing the DOE. The arrangement of the threaded retaining ring ensures that the DOE will not be displaced due to vibration or other external factors during operation, ensuring the stability of the optical system. And through the integrated fixing method, the operator can quickly switch the DOE without worrying about the loosening or displacement of the components, thereby optimizing the overall workflow.
[0094] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing what is disclosed herein. The present disclosure is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure. The specification and embodiments are to be considered merely as exemplary, and the present disclosure is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes may be made without departing from the scope thereof.
Claims
1. An additively manufactured nickel-based high-temperature alloy single crystal component having the following grain boundary structure characteristics: In the range of grain boundary angles from 15° to 30°, the grain boundary length density does not exceed 35.2 (1 / mm); In the grain boundary angle range above 30°, the grain boundary length density does not exceed 2.6 (1 / mm).
2. A powder for additive manufacturing of the nickel-based high-temperature alloy single crystal component according to claim 1, wherein the composition of the powder comprises the following elements by weight percentage: Chromium (Cr): 12wt%~14wt%, Molybdenum (Mo): 4.5wt%~5.7wt%, Niobium (Nb): 1.5wt% to 2.3wt%, Aluminum (Al): 5.5wt% to 6.5wt%, Titanium (Ti): 0.5wt% to 1wt%, Carbon (C): 0.1wt% to 0.28wt%, Zirconium (Zr): 0.02wt% to 0.1wt%, Boron (B): ≤ 0.01wt%, Silicon (Si): ≤0.5wt%, Manganese (Mn): ≤0.25wt%, Iron (Fe): ≤2.5wt%, Copper (Cu): ≤0.5wt%, Nickel (Ni): balance.
3. The powder according to claim 2, wherein the constituent elements of the powder include one or more selected from the following: The carbon (C) is selected to be 0.1wt% to 0.19wt%. Molybdenum (Mo) is selected to be 4.5wt% to 5.1wt%, Boron (B) is selected to be 0.001wt% to 0.01wt%, Zirconium (Zr) is selected as 0.05wt% to 0.1wt%, Niobium (Nb) is selected to be 1.8wt% to 2.3wt%.
4. A powder for additive manufacturing of the nickel-based high-temperature alloy single crystal component according to claim 1, wherein the composition of the powder comprises the following elements by weight percentage: Chromium (Cr): 15.7wt% to 16.3wt%, Aluminum (Al): 3.2wt%~3.7wt%, Titanium (Ti): 3.2wt% to 3.7wt%, Molybdenum (Mo): 1.5wt%~2.5wt%, Niobium (Nb): 0.6wt% to 1.4wt%, Zirconium (Zr): 0.02wt% to 0.1wt%, Boron (B): 0.003wt% to 0.015wt%, Carbon (C): 0.05wt% to 0.13wt%, Tantalum (Ta): 1.5wt%~2.3wt%, Tungsten (W): 2.4wt%~3.0wt%, Cobalt (Co): 2.0wt%~8.0wt%, Iron (Fe): ≤0.05wt%, Manganese (Mn): ≤0.02wt%, Silicon (Si): ≤0.3wt%, Sulfur (S): ≤0.015wt%, Nickel (Ni): balance.
5. The powder according to claim 4, wherein the constituent elements of the powder include one or more selected from the following: Molybdenum (Mo) is selected to be 1.6wt% to 2.1wt%, Niobium (Nb) is selected to be 0.7wt% to 1.2wt%, Carbon (C) is selected to be 0.08wt% to 0.12wt%, Tantalum (Ta) is selected as 1.6wt% to 2.1wt%, Tungsten (W) is selected to be 2.5wt% to 2.9wt%, Zirconium (Zr) is selected as 0.02wt% to 0.07wt%, Boron (B) is selected to be 0.003wt% to 0.011wt%, Cobalt (Co) is selected to be 2.0wt% to 6.0wt%.
6. The powder according to claim 4, wherein the combination of aluminum and titanium (Al+Ti) is selected to be 6.5 wt% to 7.4 wt%.
7. A method for additively manufacturing a powder-formed nickel-based high-temperature alloy single crystal component according to any one of claims 2 to 6, the method comprising: According to the preset scanning path and process parameters, the laser beam shaped by the diffractive optical element in the form of a flat-top spot is controlled at least during the additive manufacturing process to selectively melt the powder layer by layer on the substrate to form stacked and consolidated layers until the single crystal component is manufactured.
8. The method according to claim 7, wherein the process parameters include one or more of laser power 50-500 W, laser scanning speed 50-1500 mm / s, scanning line spacing 0.02-0.18 mm, layer thickness 40-60 μm, spot diameter 50-1000 μm, ratio of molten pool width to molten pool depth 2-5, ratio of molten pool width to scanning line spacing 2-5, and ratio of molten pool depth to layer thickness 1.1-3.
9. A device used in the method of claim 7 or 8 to implement the switching of the diffractive optical element, the device being constructed in the optical path before the laser beam enters the deflection mirror and being configured to include: a supporting portion, the supporting portion being fixed in the optical path; a separation portion, the separation portion being detachably fixed to the support portion; as well as a mounting portion, the mounting portion being fixed on the separating portion and used for mounting the diffractive optical element; When the diffractive optical element is switched, the diffractive optical element is separated from the optical path by detaching the separation portion from the support portion. 10 . The device according to claim 9 , wherein the supporting portion is fixed between a beam expander and a deflection mirror in the optical path and is not disassembled when the diffractive optical element is switched.
11. The device according to claim 9, wherein the mounting portion comprises at least one displacement adjuster for adjusting the displacement of the diffractive optical element in the X-axis and / or Y-axis directions. 12 . The device according to claim 9 , wherein the separation portion is embedded in the support portion so that the diffractive optical element is embedded in at least a portion of the groove of the support portion in an installed state.
13. An additive manufacturing device comprising the apparatus according to any one of claims 9 to 12.
Citation Information
Patent Citations
Diffractive optical element for shaping gauss beam into flat-topped beam, and preparation method thereof
CN103399406A
High-gamma'-content nickel-based high-temperature alloy powder for additive manufacturing, using method therefore and nickel-based high-temperature alloy component
CN112921206A
Laser additive manufacturing method for aluminum alloy based on liquid crystal dynamic regulation and control of laser beams
CN116511523A
Rapid material development process for additive manufactured materials
US20210362242A1
Cited By
Method and component for additive manufacturing of single crystal or near single crystal superalloys
CN122703021A